As 2000 approaches millennial conjuctures and apocalyptic prophecy - Berry, Brian J.
The conjunctures in question are the approach of a new millennium and the likely sag of the economy into a long-wave (Kondratiev) trough as that millennium arrives. Will there be yet another wave of apocalyptic expectation? An answer is sought in the nature and extent of American prophecy belief and in historic associations between millennial surges and long-wave troughs.